The Influence of Three Dimensional Aspects of Main Character in the Plot of “Birds of Prey” Movie - I Gusti Ayu Andhini Loka Pramurti (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2022)
The movie Birds of Prey contains a unique story with an uncommon main character who experiences a lot of things in her life throughout the plot. In which it involves the three dimensional aspects of the main character, such as; physiological, sociological, and psychological aspects. As the aims of this research are: (1) to analyze the three dimensional aspects present in the main character of Birds of Prey movie, (2) to analyze how the plot are developed based on the three dimensional aspects of the main character in Birds of Prey movie. This research was conducted by applying the qualitative method. The writer also uses two theories in this study, the first is the theory of three dimensional aspects of the main character by Egri (1946) and the second is the theory of plot proposed by Freytag (1895). Based on the result of this study, the writer found that physiologically, Harley is a pretty woman with an uncommon makeup and style. Sociologically, Harley is living miserably and surrounded by people who want to take revenge because she has no one to protect her since the breakup with Joker. Psychologically, Harley is seen as a brave woman because no matter how hard her life is, she always try to moves forward and live to the fullest. She is also smart, as she is a former psychiatrist. Though sometimes she does something crazy that is beyond imagination, she always has a way to overcome all of her problems in life. While, the plot consists of exposition, rising action, climax, falling action, and denouement, in which each of these points are strongly correlated with the three dimensional aspects of main character to make a good storyline.